Comparison of Cognitive Functions, Sleep Quality, Emotional State, Balance and Physical Activity Levels of University Students According to Academic Success. - Oksuz, Sevim; Depreli, Ozde; Ozdil, Aytül; Iyigun, Gozde; Angın, Ender; Bilgin, Betül Fatma; Karaman, Ayşen (Internet Journal of Allied Health Sciences & Practice, 2025)
Purpose: This study was planned to compare the level of attention, dual-task abilities, sleep quality, emotional state (anxiety, depression, stress), dynamic balance, and physical activity level in low and high-academic success university students. Method: A total of 134 international undergraduate students between the age of 18 and 25 (low academic success group n=67, high academic success group n=67) were recruited for this study. The Trail Making Test (TMT) -- A and B was used for attention assessment, the TMT While Walking -- A and B was utilized for dual-task performance, the Pittsburgh Sleep Quality Index (PSQI) was utilized to assess sleep quality, the Depression Anxiety and Stress Scale (DASS-21) was employed to evaluate emotional state, the Y Balance Test (YBT) was conducted to measure dynamic balance, and the International Physical Activity Questionnaire -Short Form (IPAQ-SF) was administered to determine the level of physical activity. Results: Students with high academic success had lower TMT-B and TMT-B while walking, PSQI, depression and anxiety sub-parameters of DASS-21 and total DASS-21 scores and higher YBT scores (p≤0.05) compared to those with low academic success. No significant difference was found in TMT-A and TMT-A while walking duration, stress sub-parameter of DASS-21 and IPAQ scores between the groups (p>0.05). Conclusion: In this study, students with high academic success had higher levels of attention and dual-task abilities, better sleep quality and dynamic balance, and lower levels of depression and anxiety.